The Establishment and Practice of Pharmacy Care Service Based on Internet Social Media: Telemedicine in Response to the COVID-19 Pandemic - Li, Huibo; Zheng, Siqian; Li, Da; Jiang, Dechun; Liu, Fang; Guo, Wei; Zhao, Zhenying; Zhou, Yanfei; Liu, Jingting; Zhao, Rongsheng (Frontiers in Pharmacology, 2021)
Objective: For patients with chronic diseases requiring long-term use of medications who are quarantined at home, the management of medication therapy during the COVID-19 pandemic is a problem that pharmacists urgently need to discuss and solve. The study aims to establish and launch a telepharmacy framework to implement pharmaceutical care during the COVID-19 pandemic. Methods: To establish a remote pharmacy service model based on a medication consultation service platform under the official account of the "Beijing Pharmacists Association" on the social software WeChat app, obtain the medication consultation records from February 28 to April 27, 2020, during the worst period of the epidemic in China, and to perform a statistical analysis of the information about the patients seeking consultation, consultation process, content and follow-up results. Results: The medication consultation service system based on social software was established in February 2020. The "Cloud Pharmacy Care" platform had 1432 views and 66 followers and completed 39 counseling cases in two months. Counseling was available for patients of all ages. Of the 39 cases, 82.05% of patients were young and middle-aged. During the COVID-19 pandemic, the long-term medication usage problems of patients with chronic disease were effectively addressed using "Cloud Pharmacy Care". In the consultation, 35 cases (89.7%) were related to the use of medicines or health products, and 4 cases (10.3%) involved disease state management and the use of supplements. The top five drug-related issues included the selection of medications, the dosage and usage of drugs, medications for special populations, medication therapy management of chronic diseases, and adverse drug reactions. All consultations were completed within 4 hours, with a positive review rate of 97.4%. Conclusion: During the COVID-19 pandemic, "Cloud Pharmacy Care" based on the social software WeChat app was quickly constructed and applied to solve the medication-related problems of patients and the public during home quarantining. The significance lies in the timely and interactive consultation model that helps to carry out medication therapy management for chronically ill patients and improves patients' medication compliance, improves medical quality, and plays a positive role in promoting the popularization of safe medication knowledge.